ANALISIS KEBUTUHAN PENGEMBANGAN E-MODUL LITERASI BACA TULIS VOKASIONAL BERBASIS GAME UNTUK SMK NEGERI JATENG DI PURBALINGGA - Jiwandono, Garda Tegar Jiwandono; Memet Sudaryanto; Nia Ulfa Martha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of 21st-century technology requires innovation in vocational education, particularly in strengthening reading and writing literacy skills that are relevant to workplace demands. However, literacy activities in vocational schools are still dominated by conventional learning materials and have not been optimally integrated with vocational contexts or digital approaches. This study aims to analyze teachers’ and students’ needs for the development of a game-based vocational reading and writing literacy e-module at SMK Negeri Jateng Di Purbalingga. The research employed a research and development (R&D) approach using the ADDIE model, focusing on the analysis stage. Data were collected through interviews, questionnaires, and observations involving two Indonesian language teachers and students from grades X and XI. Qualitative data were analyzed descriptively, while quantitative data were analyzed using percentage techniques. The findings reveal that both teachers and students perceive the development of a game-based digital literacy module integrated with vocational content as highly necessary. Teachers emphasized the need for contextual, interactive, and industry-relevant learning materials, while students expressed strong interest in game-based learning to support literacy activities. Therefore, a game-based vocational reading and writing literacy e-module has strong potential to enhance students’ motivation, engagement, and literacy competence in vocational education.